Community museums in Boruca and Curré/Yimba, Costa Rica: recent development, community participation, and self-determination - Martínez-Villarreal, Ronald (2024)
The aim of the article is to position the work of community museums in the indigenous territories of Boruca and Curré/Yimba in Costa Rica as key players in community development projects and deeply linked to communal life. To this end, an analysis of their recent work experience is conducted. The study is framed within a qualitative paradigm and adopts an exploratory approach focused on interviews conducted with members of the working committees. These interviews were examined based on three main components: the concept of the community museum, learning and coexistence, and community historical memory. The results highlight the role of community museums as alternative spaces for the management of memory and culture, characterized by their emphasis on community participation and experiential learning. This higlights the need to respect the essence of these museums, as they constitute strategies for self-determination. Furthermore, their integration into an intercultural vision is proposed, encompassing both the history and management of cultural heritage.